Quantitative biokinetics of titanium dioxide nanoparticles after intravenous injection in rats: Part 1. Issue 4 (21st April 2017) - Kreyling, Wolfgang G.; Holzwarth, Uwe; Haberl, Nadine; Kozempel, Ján; Hirn, Stephanie; Wenk, Alexander; Schleh, Carsten; Schäffler, Martin; Lipka, Jens; Semmler-Behnke, Manuela; Gibson, Neil
Abstract: Submicrometer TiO2 particles, including nanoparticulate fractions, are used in an increasing variety of consumer products, as food additives and also drug delivery applications are envisaged. Beyond exposure of occupational groups, this entails an exposure risk to the public. However, nanoparticle translocation from the organ of intake and potential accumulation in secondary organs are poorly understood and in many investigations excessive doses are applied. The present study investigates the biokinetics and clearance of a low single dose (typically 40–400 μg/kg BW) of 48 V-radiolabeled, pure TiO2 anatase nanoparticles ([ 48 V]TiO2 NP) with a median aggregate/agglomerate size of 70 nm in aqueous suspension after intravenous (IV) injection into female Wistar rats. Biokinetics and clearance were followed from one-hour to 4-weeks. The use of radiolabeled nanoparticles allowed a quantitative [ 48 V]TiO2 NP balancing of all organs, tissues, carcass and excretions of each rat without having to account for chemical background levels possibly caused by dietary or environmental titanium exposure. Highest [ 48 V]TiO2 NP accumulations were found in liver (95.5%ID after one day), followed by spleen (2.5%), carcass (1%), skeleton (0.7%) and blood (0.4%). Detectable nanoparticle levels were found in all other organs. The [ 48 V]TiO2 NP content in blood decreased rapidly after 24 h while the distribution in other organs and tissues remained rather constant until day-28. The present biokinetics study is part 1 of a series of studies comparing biokinetics after three classical routes of intake (IV injection (part 1), ingestion (part 2), intratracheal instillation (part 3)) under identical laboratory conditions, in order to test the common hypothesis that IV-injection is a suitable predictor for the biokinetics fate of nanoparticles administered by different routes. This hypothesis is disproved by this series of studies.